2013
DOI: 10.1007/s11829-013-9264-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of the invasive buff-tailed bumblebee (Bombus terrestris) on the pollination of the native Chilean herb Mimulus luteus

Abstract: Artículo de publicación ISI.The arrival of exotic pollinators to new habitats may introduce new patterns of floral preference and foraging behavior that modify the structure of the resident plant-pollinator community. The aim of this paper is to examine the potential impact of the exotic bumblebee Bombus terrestris on the pollination service provided by the native pollinator assemblage of the herb Mimulus luteus. The study was performed in a high-elevation locality in the Chilean Andes during the summer season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…First, despite native plants and E. vulgare sharing the more abundant pollinators, which could contribute to HP transfer among individuals , these pollinators may act as ineffective pollen carriers. This could be the case for Bombus terrestris (exotic in Chile), which visits both native and exotic flowers in invaded patches and has been determined to be an ineffective pollinator for other plant species in Mediterranean-type ecosystems of central Chile (Esterio et al 2013) and several other geographic regions around world (Goulson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, despite native plants and E. vulgare sharing the more abundant pollinators, which could contribute to HP transfer among individuals , these pollinators may act as ineffective pollen carriers. This could be the case for Bombus terrestris (exotic in Chile), which visits both native and exotic flowers in invaded patches and has been determined to be an ineffective pollinator for other plant species in Mediterranean-type ecosystems of central Chile (Esterio et al 2013) and several other geographic regions around world (Goulson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Esterio et al . () recorded the visitation rate and pollen transfer effectiveness of bees and bumblebees in a population of M. luteus during 2010, 2011 and 2012. González et al .…”
Section: A Review Of the Evidencementioning
confidence: 99%
“…Esterio et al . () examined the potential impact of the exotic bumblebee B. terrestris on the pollination service provided by the native pollinator assemblage on the herb M. luteus during three consecutive years. Results revealed that B. terrestris was an inefficient pollinator in comparison to native bees due to the small amount of pollen delivered to stigmas and the low and intermittent visitation rate over the years studied.…”
Section: A Review Of the Evidencementioning
confidence: 99%
“…Conversely, the pollinators with low visit densities likely perform a high level of pollination services if they have a high pollen transfer efficacy (Esterio et al. ). Therefore, when exploring pollinator contributions to plants, visit density and pollen transfer efficacy must to be considered collectively (Freitas ; Woodcock et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a high visit density does not result in a high level of pollination services if the pollinators carry a low number of pollen grains on their body surfaces and thus deposit a low amount of pollen grains on stigmas (Bischoff et al 2012;King et al 2013). Conversely, the pollinators with low visit densities likely perform a high level of pollination services if they have a high pollen transfer efficacy (Esterio et al 2013). Therefore, when exploring pollinator contributions to plants, visit density and pollen transfer efficacy must to be considered collectively (Freitas 2013;Woodcock et al 2013).…”
Section: Introductionmentioning
confidence: 99%